"He didn't know what he was doin'": Student perspectives of a White teacher's Hip-Hop class. (November 2020) - Kruse, Adam J
In this article, I share findings from a research study about a high school Hip-Hop course in the United States and offer considerations toward informing culturally responsive teaching and decentering Whiteness in music education. I explored the experiences and perceptions of majority students of color in a Hip-Hop course taught by a White music educator who was largely inexperienced with Hip-Hop. I was curious to understand how the students saw their teacher, what they experienced as strengths and weaknesses of the course, and what they felt they took away from the experience. I designed the qualitative study employing elements of Hip-Hop musical practices (sampling and remixing), analyzed data informed by Hip-Hop vocal techniques (doubling and ad-libbing), and structured findings based on Hip-Hop aesthetic principles (flow and rupture). Overall, students appreciated the teacher's acknowledgment of his lack of Hip-Hop experience and his ability to prioritize their perspectives and voices. They reported gaining valuable musical experiences in the course as well as developing cross-cultural competence to better understand their fellow students.